Statin therapy in patients with acute coronary syndrome: low-density lipoprotein cholesterol goal attainment and effect of statin potency - Chinwong D; Patumanond J; Chinwong S; Siriwattana K; Gunaparn S; Hall JJ; Phrommintikul A (Dove Medical Press, 2015)
Dujrudee Chinwong,1,2 Jayanton Patumanond,3 Surarong Chinwong,1 Khanchai Siriwattana,4 Siriluck Gunaparn,5 John Joseph Hall,6 Arintaya Phrommintikul5 1Department of Pharmaceutical Care, Faculty of Pharmacy, Chiang Mai University, Chiang Mai, Thailand; 2Clinical Epidemiology Program, Faculty of Medicine, Chiang Mai University, Chiang Mai, Thailand; 3Center of Excellence in Applied Epidemiology, Faculty of Medicine, Thammasat University, Pathum Thani, Thailand; 4Division of Medicine, Nakornping Hospital, Chiang Mai, Thailand; 5Department of Internal Medicine, Faculty of Medicine, Chiang Mai University, Chiang Mai, Thailand; 6Centre for Clinical Epidemiology and Biostatistics, School of Medicine and Public Health, Faculty of Health, University of Newcastle, Callaghan, NSW, Australia Background: Elevated low-density lipoprotein cholesterol (LDL-C) is associated with an increased risk of coronary artery disease. Current guidelines recommend an LDL-C target of <70 mg/dL (<1.8 mmol/L) for acute coronary syndrome (ACS) patients, and the first-line treatment to lower lipids is statin therapy. Despite current guidelines and the efficacious lipid-lowering agents available, about half of patients at very high risk, including ACS patients, fail to achieve their LDL-C goal. This study assessed LDL-C goal attainment according to use of high and low potency statins in routine practice in Thailand.Methods: A retrospective cohort study was performed by retrieving data from medical records and the electronic hospital database for a tertiary care hospital in Thailand between 2009 and 2011. Included were ACS patients treated with statins at baseline and with follow-up of LDL-C levels. Patients were divided into high or low potency statin users, and the proportion reaching the LDL-C goal of <70 mg/dL was determined. A Cox proportional hazard model was applied to determine the relationship between statin potency and LDL-C goal attainment. Propensity score adjustment was used to control for confounding by indication.Results: Of 396 ACS patients (60% males, mean age 64.3±11.6 years), 229 (58%) were treated with high potency statins and 167 (42%) with low potency statins. A quarter reached their target LDL-C goal (25% for patients on high potency statins and 23% on low potency statins). High potency statins were not associated with increased LDL-C goal attainment (adjusted hazards ratio 1.22, 95% confidence interval 0.79–1.88; P=0.363).Conclusion: There was no significant effect of high potency statins on LDL-C goal attainment. Moreover, this study showed low LDL-C goal attainment for patients on either low or high potency statins. The reasons for the low LDL-C goal attainment rate warrants further investigation. Keywords: LDL-C goal attainment, statins, potency statins, high risk, propensity score